Mengukur Keberhasilan Evaluasi Pembelajaran: Telaah Evaluasi Formatif Dan Sumatif Dalam Kurikulum Merdeka - Firani Putri; Supratman Zakir (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Assessment is a series of activities to obtain, analyze and interpret data about student learning processes and outcomes which are carried out systematically and continuously, so that it becomes meaningful information in decision making. In the independent curriculum there are types of assessments as learning evaluations, namely: Formative Assessment and Summative Assessment. The purpose of this discussion is for educators to think about and plan appropriate formative and summative assessments for students. Then, educators should use formative and summative assessment techniques in accordance with the function and objectives of the assessment, the results of the assessment can be interpreted and bring benefits to students. The method use in this research is qualitative method by examining documents in the form of books, literature and scientific journals as secondary data which analyzed using content analysis. The research results and research conclusions in outlining the definition of formative assessment are data obtained in the learning process which will be interpreted by educators in order to decide on effective learning activities for students. Summative Assessment is an activity to assess the achievement of learning objectives and/or Learning Outcomes (CP) of students, as a basis for determining grade promotion and/or graduation from an educational unit. Formative assessment techniques; Goal Checks, Individual Discussion, Observation, Group Presentation and Self-assessment, while summative assessment techniques; Written tests, Portfolio, Performance and Projects. The usefulness of formative and summative assessments is to monitor, identify, analyze and improve the learning process, as well as evaluate the achievement of learning goals for students.